MAIT Cells Balance the Requirements for Immune Tolerance and Anti-Microbial Defense During Pregnancy - Raffetseder, Johanna; Lindau, Robert; van der Veen, Sigrid; Berg, Göran; Larsson, Marie; Ernerudh, Jan (Frontiers in Immunology, 2021)
Mucosal-associated invariant T (MAIT) cells are an innate-like T cell subset with proinflammatory and cytotoxic effector functions. During pregnancy, modulation of the maternal immune system, both at the fetal-maternal interface and systemically, is crucial for a successful outcome and manifests through controlled enhancement of innate and dampening of adaptive responses. Still, immune defenses need to efficiently protect both the mother and the fetus from infection. So far, it is unknown whether MAIT cells are subjected to immunomodulation during pregnancy, and characterization of decidual MAIT cells as well as their functional responses during pregnancy are mainly lacking. We here characterized the presence and phenotype of Vα7.2+CD161+ MAIT cells in blood and decidua (the uterine endometrium during pregnancy) from women pregnant in the 1st trimester, i.e., the time point when local immune tolerance develops. We also assessed the phenotype and functional responses of MAIT cells in blood of women pregnant in the 3rd trimester, i.e., when systemic immunomodulation is most pronounced. Multi-color flow cytometry panels included markers for MAIT subsets, and markers of activation (CD69, HLA-DR, Granzyme B) and immunoregulation (PD-1, CTLA-4). MAIT cells were numerically decreased at the fetal-maternal interface and showed, similar to other T cells in the decidua, increased expression of immune checkpoint markers compared with MAIT cells in blood. During the 3rd trimester, circulating MAIT cells showed a higher expression of CD69 and CD56, and their functional responses to inflammatory (activating anti-CD3/CD28 antibodies, and IL-12 and IL-18) and microbial stimuli (Escherichia coli, group B streptococci and influenza A virus) were generally increased compared with MAIT cells from non-pregnant women, indicating enhanced antimicrobial defenses during pregnancy. Taken together, our findings indicate dual roles for MAIT cells during pregnancy, with an evidently well-adapted ability to balance the requirements of immune tolerance in parallel with maintained antimicrobial defenses. Since MAIT cells are easily activated, they need to be strictly regulated during pregnancy, and failure to do so could contribute to pregnancy complications.